2022
DOI: 10.1111/jcmm.17334
|View full text |Cite
|
Sign up to set email alerts
|

Human breast milk‐derived exosomes through inhibiting AT II cell apoptosis to prevent bronchopulmonary dysplasia in rat lung

Abstract: Human breast milk (HBM) effectively prevents and cures neonatal bronchopulmonary dysplasia (BPD). Exosomes are abundant in breast milk, but the function of HBM‐derived exosomes (HBM‐Exo) in BPD is still unclear. This study was to investigate the role and mechanism of HBM‐Exo in BPD. Overall lung tissue photography and H&E staining showed that HBM‐Exo improved the lung tissue structure collapse, alveolar structure disorder, alveolar septum width, alveolar number reduction and other injuries caused by high oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Apart from higher concentrations of leukotriene, endothelin-1[ 32 ], IL-6[ 33 ], and IL-17 A [ 34 , 35 ], newborns destined for BPD also exhibit an increase in the number of circulating neutrophils and macrophages. During the alveolar phase (lung development is not mature), the increase in IL-17 A activates the IL-17 signaling pathway, causing inflammation, which may further affect lung development and lead to the occurrence of BPD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from higher concentrations of leukotriene, endothelin-1[ 32 ], IL-6[ 33 ], and IL-17 A [ 34 , 35 ], newborns destined for BPD also exhibit an increase in the number of circulating neutrophils and macrophages. During the alveolar phase (lung development is not mature), the increase in IL-17 A activates the IL-17 signaling pathway, causing inflammation, which may further affect lung development and lead to the occurrence of BPD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the alveolar phase (lung development is not mature), the increase in IL-17 A activates the IL-17 signaling pathway, causing inflammation, which may further affect lung development and lead to the occurrence of BPD [ 36 ]. Recent studies have found that IL-17 A level is significantly upregulated and the IL-17 signaling pathway is significantly activated in the external circulation of children with BPD [ 10 , 34 , 35 ]. In the BPD mouse model, the expression of Th17 cells was enhanced in lung, demonstrating strong pro-inflammatory properties and resistance to Treg mediated inhibition [ 13 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity may be the main mechanism by which breast milk decreases the risk of BPD (42) . Although BPD is multifactorial in origin, it has been suggested that the association between breast-feeding and BPD is related to the presence of antioxidant components such as the exosomes in breast milk, which exert a protective role on the type II alveolar epithelium (43) . From an epidemiological standpoint, the prevalence of late sepsis and NEC is reported to be lower in VLBW infants fed with breast milk (44,45) , due to the shorter period spent in the neonatal intensive care unit, with fewer days of mechanical ventilation and oxygen therapy (46) , and hence a lower risk of BPD, observations in line with our results.…”
Section: Changing Epidemiology Of Bronchopulmonary Dysplasia Over The...mentioning
confidence: 99%
“…This is particularly relevant considering that BPD is an increasingly common respiratory adverse outcome that prolongs NICU stays and particularly impacts rehospitalization, as well as long-term lung and neurological outcomes. In a study conducted on rats [ 28 ], the role of HBM-Exo in the protective action of breast milk on BPD was investigated, and the results were also encouraging about the possibility of a new therapeutic approach to BPD. HBM-Exo histochemically promoted the proliferation of AT II cells and inhibited their apoptosis through IL-17 regulation, and in the overall picture, it improved the appearance of structural lesions in the lung tissue.…”
Section: Maternal Milk Feeding and Outcomes In Very Low Birth Weight ...mentioning
confidence: 99%